2013
DOI: 10.1007/s00590-013-1372-1
|View full text |Cite
|
Sign up to set email alerts
|

Early MRI diagnostics for suspected scaphoid fractures subsequent to initial plain radiography

Abstract: The introduction of early MRI enhances scaphoid injury diagnostics and accelerates patient management. We therefore endorse the introduction of this approach on a wider scale through an update of the clinical guidelines for scaphoid injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…14,15 NICE guidelines recommend MRI as the imaging modality of choice if plain radiographs are normal. 4 There is increasing demand for this resource, acutely and electively, within orthopaedics, as well as other specialties, making time in the scanner very precious. The SUSPECT study group recently found that only a minority of emergency departments in the UK have direct availability of MRI scans to diagnose clinically suspected scaphoid fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 NICE guidelines recommend MRI as the imaging modality of choice if plain radiographs are normal. 4 There is increasing demand for this resource, acutely and electively, within orthopaedics, as well as other specialties, making time in the scanner very precious. The SUSPECT study group recently found that only a minority of emergency departments in the UK have direct availability of MRI scans to diagnose clinically suspected scaphoid fractures.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is considered the gold standard of imaging methods for demonstrating occult scaphoid pathology, with the National Institute for Clinical Excellence (NICE) recommending early consideration of MRI in the assessment of potential scaphoid fracture. 4 However, MRI scans are costly and the demand for the service is high, with limited accessibility to scanners within most NHS institutions.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has revealed that 16% of scaphoid fractures may be radiographi-cally occult. 20 Stevenson et al 21 recommended early CT test to manage suspected occult scaphoid fractures for its accurate diagnosis, while Fallahi et al 22 considered that MRI scan should play a major role in the management of clinically suspected scaphoid fracture. For this reason, one should have a high level of suspicion when assessing young patients with radial wrist pain, and CT or MRI should be obtained to further assess for a nondisplaced scaphoid fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the department can avoid overtreatment of the patient, which can include needless immobilization, and undertreatment of the patient, which can lead to complications such as non-union. However, recent studies suggested using MRI to diagnose scaphoid fracture ( 12 , 17 , 19 ). Future studies that use a larger sample size are needed to determine the value of clinical examination and plain radiographs in the diagnosis of scaphoid fracture.…”
Section: Discussionmentioning
confidence: 99%